1976
DOI: 10.1001/archderm.112.9.1286
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of relapsing polychondritis with dapsone

Abstract: Three patients with relapsing polychondritis were treated successfully with dapsone. Mounting evidence suggests an immune-related pathogenesis for relapsing polychondritis. Dapsone may be effective in certain immune-related diseases because of its inhibition of lysosomal enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Dapsone and colchicine may also be used in these patients. Dapsone in doses of 50 to 200 mg/day has been advocated as an effective initial therapy in patients without cardiorespiratory involvement [69][70][71] but Trentham et al [3] observed that it was not effective in most patients and resulted in a number of adverse reactions. Organ-threatening disease, including severe polychondritis, ocular or laryngotracheal involvement and systemic vasculitis require systemic corticosteroids.…”
Section: Managementmentioning
confidence: 99%
“…Dapsone and colchicine may also be used in these patients. Dapsone in doses of 50 to 200 mg/day has been advocated as an effective initial therapy in patients without cardiorespiratory involvement [69][70][71] but Trentham et al [3] observed that it was not effective in most patients and resulted in a number of adverse reactions. Organ-threatening disease, including severe polychondritis, ocular or laryngotracheal involvement and systemic vasculitis require systemic corticosteroids.…”
Section: Managementmentioning
confidence: 99%
“…Zahlreiche immunsuppressive Therapien wie Azathioprin, Cyclophosphamid, Cyclosporin, Methotrexat, Plasmapherese, Dapsone sind mit unterschiedlichem Erfolg als Mono-und Kombinationstherapie eingesetzt worden, wobei aufgrund der geringen Fallzahlen keine verlässlichen Therapiestudien vorliegen [33][34][35][36][37]. In den letzten Jahren wurde das Behandlungskonzept um die "Bi-…”
Section: Relapsing Polychondritis · Vasculitisunclassified
“…The dramatic efficacy of dapsone, both in RP [12,13] and in DH [14] merits con sideration. Dapsone most likely acts in DH via inhibition of myeloperoxidase in poly morphonuclear leukocytes [15], which prob ably plays a role in the bullous lesion.…”
Section: Commentmentioning
confidence: 99%